2016
DOI: 10.15448/1980-6108.2015.3.21176
|View full text |Cite
|
Sign up to set email alerts
|

Medidas antropométricas em idosos assistidos na atenção básica e sua associação com gênero, idade e síndrome da fragilidade: dados do EMI-SUS

Abstract: Este artigo está licenciado sob forma de uma licença Creative Commons Atribuição 4.0 Internacional, que permite uso irrestrito, distribuição e reprodução em qualquer meio, desde que a publicação original seja corretamente citada. RESUMOObjetivos: Descrever medidas antropométricas em idosos assistidos na atenção básica e analisar sua associação com gênero, idade e síndrome da fragilidade. Métodos: Este estudo transversal é parte do Estudo Epidemiológico e Clínico dos Idosos Atendidos pela Estratégia Saúde da F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 71 publications
(162 reference statements)
0
6
0
6
Order By: Relevance
“…Of all the articles with captive populations, 4 of these included elderly people 39 , 42 , 44 , 45 and also reported the mean NC. The minimum and maximum mean NC in this captive population were 34.60cm and 36.94cm, respectively; in men were 39.19cm and 40.20cm, respectively; and in women the minimum and maximum values were 33.50cm and 36.38cm, respectively ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of all the articles with captive populations, 4 of these included elderly people 39 , 42 , 44 , 45 and also reported the mean NC. The minimum and maximum mean NC in this captive population were 34.60cm and 36.94cm, respectively; in men were 39.19cm and 40.20cm, respectively; and in women the minimum and maximum values were 33.50cm and 36.38cm, respectively ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…From all the cross-sectional studies, only 4 studies 19 , 22 , 25 , 29 are considered as a close representation of the general population. Finally, analyzing the risk of bias of the prevalence studies included, the majority represent a moderate risk 17 , 24 , 29 31 , 33 , 35 – 43 , 45 , 47 , 48 , 50 – 51 , 53 66 , 68 , 70 73 , 76 – 84 , 86 , 89 , 92 – 100 (57); some are low risk 16 , 18 23 , 25 29 , 32 , 34 , 44 , 49 (16); no study represents a high risk ( Table 4 – Table 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another analysis of anthropometric measurements performed in elders from the city of Porto Alegre/RS shows that the average BP took the value of 31.51±4,25cm, classifying these individuals into an interval between eutrophy and overweight, considering the Standard Deviation 12 . This datum corroborates the finding of initial and final assessment in this case study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study, evaluating the association of anthropometric measurements with frailty, in the same population, demonstrated that frailty was associated with muscle mass loss. The frail elderly had lower measures of size and complexion [ 32 ]. This pattern of increase of intramuscular and visceral fat with aging is accompanied by changes in subcutaneous fat, which can be evaluated through the measurement of BS [ 33 ].…”
Section: Discussionmentioning
confidence: 99%